IL-21 induces death of marginal zone B cells during chronic inflammation. - Tortola, L; Yadava, K; Bachmann, M; Müller, C; Kisielow, J; Kopf, M (2010)
Interleukin-2 (IL-2) and IL-21 share activities in the control of T- and B-cell maturation, proliferation, function, and survival. However, opposing roles for IL-2 and IL-21 have been reported in the development of regulatory T cells. To dissect unique, redundant, and opposing activities of IL-2 and IL-21, we compared T- and B-cell development and function in mice lacking both IL-2 receptor α (IL-2Rα) and IL-21R (double knockouts [DKO]) with single knockout and wild-type (WT) mice. Similarly to il2ra(-/-) mice, DKO showed reduced numbers of regulatory T cells and, consequently, hyper-activation and proliferation of T cells associated with inflammatory disease (ie, colitis), weight loss, and reduced survival. The absence of IL-2Rα resulted in overproduction of IL-21 by IFN-γ-producing CD4(+) T cells, which induced apoptosis of marginal zone (MZ) B cells. Hence, MZ B cells and MZ B-cell immunoglobulin M antibody responses to Streptococcus pneumoniae phosophorylcholine were absent in il2ra(-/-) mice but were completely restored in DKO mice. Our results highlight key roles of IL-2 in inhibiting IL-21 production by CD4(+) T cells and of IL-21 in negatively regulating MZ B-cell survival and antibody production.